Pengaruh Pengawasan Pajak, Teknologi Informasi Perpajakan, dan Ajaran Tamansiswa (Tri Pantangan) terhadap Tax Evasion - Sri Lestari Yuli Prastyatini; Frederik Sakario (Jurnal Literasi Akuntansi, 2024)
Purpose: This research aims to examine the influence of tax supervision, tax information technology, and Tamansiswa teachings (Tri Pantangan) on tax evasion among taxpayers registered at the Yogyakarta City Pratama Tax Service Office (KPP Pratama). Method: The research uses a quantitative approach, with a population consisting of taxpayers registered at KPP Pratama Yogyakarta City. Data was collected using a questionnaire distributed to 78 randomly selected respondents. The analysis tools used were statistical techniques to determine the relationship between tax supervision, tax information technology, and the influence of the Tri Pantangan teachings on tax evasion. Findings: The research results reveal that tax supervision has a positive influence on tax evasion, indicating that higher tax supervision correlates with a higher level of tax evasion. This suggests that tax supervision is ineffective in promoting taxpayer compliance. In contrast, tax information technology has a significant negative effect on tax evasion, as it increases efficiency and transparency, making monitoring and evaluation easier, thus reducing the chances of tax evasion. Furthermore, the teachings of Tamansiswa's Tri Pantangan, which include principles against lying, stealing, and laziness, significantly discourage tax evasion by fostering honesty and compliance among taxpayers.